(untitled) (AL MUNAZHZHARAH, 2025)
Marriage in Indonesia must be carried out in accordance with Article 2 paragraph (1) and (2) of Law Number 1 of 1974 whereby marriages carried out by men and women must be registered with the local authorities to ensure orderly administration of government and population. As well as determining the origin of children in case number 249/Pdt.P/2020/PA.Kab.Kdr, where husband and wife do not register their marriage, so problems arise when going to take care of the administration of the birth of a child in a child’s birth certificate. This study aims to analyze the examination procedure and the legal basis for the judge’s consideration in granting a case on the origins of biological children at the Kediri Regency Religious Court (case number 249/Pdt.P/2020/PA.Kab.Kdr). This type of research uses empirical legal research methods using a sociological approach. This study uses primary data types, namely interviews and secondary data, namely data from books and research articles. While the data collection techniques are observation, interviews, and documentation. Then this research was analyzed through the stages of data reduction, data validation, data clarification, and data analysis. The results and discussion of this study indicate that the legal basis is juridical and non-juridical. judges are oriented towards the protection of children’s rights by taking into account the principle of the best interests of the child both from the psychological aspect of child development as well as aspects of legislation so that the determination of the case is fair.